2009
DOI: 10.1104/pp.109.142489
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of New Maize Genes Putatively Involved in Cytokinin Metabolism and Their Expression during Osmotic Stress in Relation to Cytokinin Levels  

Abstract: Plant hormones, cytokinins (CKs), have been for a long time considered to be involved in plant responses to stress. However, their exact roles in processes linked to stress signalization and acclimatization to adverse environmental conditions are unknown. In this study, expression profiles of the entire gene families of CK biosynthetic and degradation genes in maize (Zea mays) during development and stress responses are described. Transcript abundance of particular genes is discussed in relation to the levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
118
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(136 citation statements)
references
References 55 publications
13
118
0
2
Order By: Relevance
“…However, expression patterns suggested that cZOGT2 might have a different physiological function from that of maize cisZOGs at the seedling stage: cZOGT2 was predominantly expressed in shoots (Figs. 5 and 6), whereas cisZOG genes were active mostly in roots (Veach et al, 2003;Vyroubalová et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, expression patterns suggested that cZOGT2 might have a different physiological function from that of maize cisZOGs at the seedling stage: cZOGT2 was predominantly expressed in shoots (Figs. 5 and 6), whereas cisZOG genes were active mostly in roots (Veach et al, 2003;Vyroubalová et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Although recent studies with nonmodel plants suggested possible roles for cZ (Vyroubalová et al, 2009;Goggin et al, 2010;Lomin et al, 2011), its physiological significance was yet to be clarified. Our root growth assay clearly demonstrated comparable activities of cZ and tZ in the inhibition of rice seminal root elongation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We focused on two model plant organisms, the moss P. patens and maize, due to the availability of detailed information on cytokinin metabolism in both species (Massonneau et al, 2004;von Schwartzenberg, 2009;Vyroubalová et al, 2009). The genome databases for the moss P. patens (www.phytozome.net, version 9.1) and maize (www.maizesequence.org, version 5b.60) indicate that these species contain three and five NRH genes, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In plant, knowledge of HINT1 protein is generally restricted to sequence analyses and the information is highly lacking, especially about the HINT1 homologue in maize. Maize (Zea mays L.) is one of the most important crop species used especially for direct human consumption and animal feed and a significant plant source for chemical feedstock (Vyroubalová et al 2009). Moreover, maize is also an important model organism for fundamental research into the inheritance and functions of genes, the physical linkage of genes to chromosomes, the mechanistic relation between cytological crossovers and recombination, origin of the nucleolus, imprinting, and transposition (Bennetzen and Hake 2009).…”
Section: Introductionmentioning
confidence: 99%